ANALISIS PENERAPAN MANAJEMEN SUPPLY CHAIN MAKANAN BEKU (FROZEN FOOD) PADA CV. MANDALA ABADI SEJAHTERA DI DESA LOA JANAN ULU - Nur Fitri, Kholifah; Fahleti, Widya; Akhmadiansyah (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2025)
This research is entitled Application of Supply Chain on CV. Mandala Abadi Sejahtera in Loa Janan Ulu Village aims to find out and describe the implementation of supply chain management in the frozen food business CV. Mandala Abadi Sejahtera which is effective and efficient and to find out and describe supply chain management in the frozen food business CV. Mandala Abadi Sejahtera in Loa Janan. The research used by researchers used qualitative descriptive methods. This type of qualitative descriptive research is a recording procedure to describe or describe the condition of a subject, and qualitative descriptive research. By conducting observations and interviews obtained, the CV frozen food supply chain. Mandala Abadi Sejahtera involves at least 5 main actors, namely suppliers, producers, distributors, retailers and final consumers. The supply chain system has not been implemented perfectly. And find out what problems there are, such as an inadequate refrigerator. In this case the supply chain still uses a conventional system in the sense of creating close ties with its suppliers. CV. Mandala Abadi Sejahtera does not have its own logistics department. Usually they deliver the products they market themselves to one agent or customer to another. Business scale and cost constraints are common reasons for UMKM not to have their own logistics department. For the efficiency that CV wants to achieve. Mandala Abadi Sejahtera is still not optimal because they do not implement supply chain management as a whole. Supply Chain Management is run by the CV business